Pedagogical technologies of formation of responsible attitude to health and healthy lifestyle in students of institutions of higher education - K.S. Gordeeva; V.M. Prystynskyi; A.V. Osiptsov (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
The purpose of the work is to establish the factors of influence, to justify the degree of formation and to test experimentally the effectiveness of pedagogical technologies for the formation of a responsible attitude towards health and a healthy lifestyle in students of institutions of higher education. Material and methods. The definition and experimental verification of the effectiveness of pedagogical technologies for the formation of a responsible attitude to the health and healthy lifestyle of students was carried out on the basis of the Department of Theoretical and Methodological Foundations of Physical Education and Rehabilitation, the Department of Human Health and Physical Education and the Scientific Research Laboratory for the Interaction of the Spiritual and Physical Development of Children and students of the "Donbass State Pedagogical University" (Slavyansk). 49 students of the second year of the faculty of physical education were involved in experimental research; 42 first and second year students of the Faculty of Psychology, Economics and Management; 57 students of the first and second years of the Faculty of Philology. Results. Indicators of the level of knowledge among students about the impact of motor activity on the state of human health are defined. The positive dynamics of the formation of the responsible attitude to health and a healthy lifestyle among students was established, in which the high level increased by an average of 19,2 % (in control groups - by 2,3 %); the number of students who developed a responsible attitude toward health corresponds to a low level in the experimental groups decreased by an average of 31,7 %, and in the control groups - by 3,1 %. Conclusions. It is confirmed that the pedagogical technologies for the formation of a responsible attitude of students to health and a healthy lifestyle are quite effective and can be introduced into the educational process of physical education of higher education institutions of III-IV levels of accreditation.